The Relationship between Grandiose and Vulnerable (Hypersensitive) Narcissism - Jauk, Emanuel; Weigle, Elena; Lehmann, Konrad; Benedek, Mathias; Neubauer, Aljoscha C. (Frontiers in Psychology, 2017)
Narcissistic grandiosity is characterized by overt expressions of feelings of superiority and entitlement, while narcissistic vulnerability reflects hypersensitivity and introversive self-absorbedness. Clinical evidence suggests that grandiosity is accompanied by vulnerable aspects, pointing to a common foundation. Subclinical personality research, however, views grandiose and vulnerable narcissism as independent traits. Grandiose narcissism displays substantial correlation with extraversion, while vulnerable narcissism correlates highly with introversion. We investigated if (1) controlling for intro-/extraversion might reveal a “common core” of grandiose and vulnerable narcissism, and if (2) the correlation between both aspects might be higher at higher levels of narcissism. Latent variable structural equation modeling and segmented regression analysis confirmed these hypotheses in a large nonclinical sample (N = 1,006). Interindividual differences in intro-/extraversion mask the common core of grandiose and vulnerable narcissism. The association between both aspects increases at high levels (10th percentile) of grandiose narcissism, which suggests a possible transition to clinically relevant (pathological) narcissism.